Pelatihan Pembuatan Pupuk Organik Cair dari Limbah Kulit Kopi di Desa Pakis Jember - Amini, Helda Wika; Rizkiana, Meta Fitri; Palupi, Bekti; Hidayati, Nurul; Raharjo, Sonya Hakim; Nurani, Yukti; Aziz, Mohamad Naufal Nizaar; Saputri, Ocha; Permatasari, Intan; Fandora, Ardan Jauza; Adriansyah, Muhamad; Nurjannah, Lailia; Rachman, Darryl Akeyla; Firmansyah, Alex; Devara, Arighy Zahirah Faiqy; Ulfiani, Khoirun Nisya' (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
Indonesia is one of the largest coffee-producing countries in the world. Indonesia recorded a large coffee harvest capacity reaching 774.96 thousand tons in 2022. The coffee processing naturally results in coffee hull waste that continues to be produced in large quantities. About 40 to 48% of the coffee hull composition contained in a coffee cherry is often discarded during processing and is not optimally utilized. One sustainable solution that can be implemented is processing coffee hull waste into liquid organic fertilizer (POC) through fermentation with EM4. This community service program was implemented in Pakis Village, Panti District, Jember Regency, which has 441.40 hectares of coffee plantations with an annual production of around 1,200 tons of robusta coffee. The program includes bioreactor development, socialization, and training for the community regarding the processing of coffee hull waste into POC. The result is increased community knowledge and skills as well as economic benefits for coffee farmers in Pakis Village through improved soil productivity. The results of the activities showed that the clarity of the knowledge with community needs increased to 70%, public interest in POC activities increased to 85%, and resulted in public satisfaction of 95%.